Estoration or Remodeling? The constitutional State in the Postmodern Era - Re, Lucia (Soft Power, 2024)
In recent years, a significant part of legal reflection has focused on the crisis of constitutional States, due in part to globalization, in part to the attack that some political forces have launched on the values of “(inter)national constitutionalism” (Mazzarese, 2018). A first reading, which we can define as optimistic, has highlighted the emergence from the crisis of a new “global law” and of international regimes able to foster a supranational protection of fundamental rights. On the contrary, a critical reading has denounced a process of de-constitutionalization overwhelming democracies. These readings are often presented as antithetical. And yet, on the one hand, each of them brings to light useful elements not only for theoretical reflection but also for the defense of (inter)national constitutionalism; on the other hand, both may underestimate the political and social dimension of the current crisis.